Analisis Etika Bisnis Industrial Hak Keamanan Pekerja Khususnya pada Karyawati - Wafiyati Nur Amrina; Halimah Zahrah; Lailafitri Pratiwi; Alifa Raudhatul Nisa; Naila Dwi Ananti (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This research examines business ethics of employee rights in industry, with a case study of PT Alpen Food Industry (AICE), a company engaged in ice cream production. Through a qualitative approach, the main focus of this research is the violation of law and business ethics against gender injustice, lack of protection of reproductive rights, and lack of access to justice in the workplace. Using a qualitative approach and analysis of business ethics and human rights theories, this research shows that the company's practices contradict the Labor Law and principles of social responsibility. The research provides policy recommendations to improve protection for women workers in the industrial sector.